Education Of Water Needs And Management For Agriculture In Garagahan Irrigation Area: Edukasi Kebutuhan Dan Pengelolaan Air Untuk Pertanian Di DaerahIrigasi Garagahan - Zuherna Mizwar; Lusi Utama (Journal of Community Service and Application of Science, 2022)
Irrigation Areas (DI) were built to meet various needs of life, especially to achieve the level of community welfare. D I Sangkir Garagahan was built by the Department of Water Resources and Construction Development in 1986 and is located in the Lubuk Basung sub-district, Agam regency. The current irrigation management is 671 hectares covering 3 working areas, namely Nagari Garagahan which has an area of ​​415 hectares of irrigated rice fields, Nagari Kampuang Tangah 136 hectares and Nagari Manggopoh 120 hectares. On April 15, 2022 an educational training was conducted to determine the needs and management of water for agricultural land. The methods used are lectures, discussions and training on the use of formulas to regulate plant water and soil management. The training was attended by the Nagari Garagahan community who are members of the Water User Farmers Association (P3A) and Water User Farmers Association (GP3A). Availability of water by adjusting plant water in the field and at the entrance gate for an area of ​​415 hectares of irrigated rice fields, the water requirement is 0.7204 m3/second. Soil management for agriculture is carried out by biological, non-biological and mechanical methods. By adjusting the capacity of the nagari for its implementation